Assessment Of Motility And Velocity Parameters Of Freshly Ejaculated Spermatozoa Of Bubalus Bubalis And Bos Indicus Bulls Through Computer Assisted Semen Analyzer - Patel, J.B.; Dhami, A.J.; Patel , P.A.; Savaliya , F.P. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Fresh semen ejaculates (90) of 15 mature bulls, 5 each of Jafarabadi, Mehsana and Crossbred (HF x Kankrej) breeds were studied for sperm motility and velocity parameters through computer assisted semen analyzer (CASA). The mean values of motile and progressively motile sperm in the semen of Jafarabadi and Mehsana buffalo bulls were significantly (P
Keywords: CASA; Buffalo-bull; Cow-bull; Fresh spermatozoa; Motility; Velocity